Pro-oxidant status and matrix metalloproteinases in apical lesions and gingival crevicular fluid as potential biomarkers for asymptomatic apical periodontitis and endodontic treatment response - Dezerega, Andrea (BioMed Central, 2012)
BACKGROUND: Oxidative stress and matrix metalloproteinases -9 and -2 are involved in periodontal breakdown, whereas gingival crevicular fluid has been reported to reflect apical status. The aim of this study was to characterize oxidant balance and activity levels of MMP -2 and -9 in apical lesions and healthy periodontal ligament; and second, to determine whether potential changes in oxidant balance were reflected in gingival crevicular fluid from asymptomatic apical periodontitis (AAP)-affected teeth at baseline and after endodontic treatment. METHODS: Patients with clinical diagnosis of AAP and healthy volunteers having indication of tooth extraction were recruited. Apical lesions and healthy periodontal ligaments, respectively, were homogenized or processed to obtain histological tissue sections. Matrix metalloproteinase -9 and -2 levels and/or activity were analyzed by Immunowestern blot, zymography and consecutive densitometric analysis, and their tissue localization was confirmed by immunohistochemistry. A second group of patients with AAP and indication of endodontic treatment was recruited. Gingival crevicular fluid was extracted from AAP-affected teeth at baseline, after endodontic treatment and healthy contralateral teeth. Total oxidant and antioxidant status were determined in homogenized tissue and GCF samples. Statistical analysis was performed using STATA v10 software with unpaired t test, Mann-Whitney test and Spearman's correlation. RESULTS: Activity of MMP-2 and MMP-9 along with oxidant status were higher in apical lesions (p < 0.05). Total oxidant status correlated positively with matrix metalloproteinase-2 and lesion size (p < 0.05). Gingival crevicular fluid showed significantly lower levels of total antioxidant status in diseased teeth at baseline compared to controls and endodontically-treated groups. CONCLUSIONS: Apical lesions display an oxidant imbalance along with increased activity of matrix metalloproteinase-2 and -9 and might contribute to AAP progression. Oxidant imbalance can also be reflected in GCF from AAP-affected teeth and was restored to normal levels after conservative endodontic treatment. These mediators might be useful as potential biomarkers for chair-side complementary diagnostic of apical status in GCF.